From carbon nanotubes and silicate layers to graphene platelets for polymer nanocomposites - Zaman - izzuddin@uthm.edu.my, Izzuddin; Kuan, Hsu-Chiang; Dai, Jingfei; Nobuyuki, Kawashima; Michelmore, Andrew; Sovi, Alex; Dong, Songyi; Lee, Luong; Jun, Ma (The Royal Society of Chemistry, 2012)
In spite of extensive studies conducted on carbon nanotubes and silicate layers for their polymer-based nanocomposites, the rise of graphene now provides a more promising candidate due to its exceptionally high mechanical performance and electrical and thermal conductivities. The present study developed a facile approach to fabricate epoxy–graphene nanocomposites by thermally expanding a commercial product followed by ultrasonication and solution-compounding with epoxy, and investigated their morphologies, mechanical properties, electrical conductivity and thermal mechanical behaviour. Graphene platelets (GnPs) of 3.57 0.50 nm in thickness were created after the expanded product was dispersed in tetrahydrofuran using 60 min ultrasonication. Since epoxy resins cured by various hardeners are widely used in industries, we chose two common hardeners: polyoxypropylene (J230) and 4,40 -diaminodiphenylsulfone (DDS). DDS-cured nanocomposites showed a better dispersion and exfoliation of GnPs, a higher improvement (573%) in fracture energy release rate and a lower percolation threshold (0.612 vol%) for electrical conductivity, because DDS contains benzene groups which create p–p interactions with GnPs promoting a higher degree of dispersion and exfoliation of GnPs during curing. This research pointed out a potential trend where GnPs would replace carbon nanotubes and silicate layers for many applications of polymer nanocomposites.